Features of Discrimination Based on Racial, National and Religious Grounds - Golubovsky, Vladimir Y.; Kunts, Elena V.; Kostyuk, Mikhail F. (Opción, 2019)
The aim of the study is to investigate the features of discrimination based on racial, national and religious grounds via a complex of general scientific (analysis, synthesis, comparison, abstraction), and special (historical, system-structural, logical, comparative legal) methods. As a result, the religious ground is important in the way that it is among such aspects of discrimination which have not as social as psychological reasons. In conclusion, the reality of discriminatory facts and processes is a sequence higher and covers almost all aspects related to the proposed classification based on the phenomenon under study.